Sexual violence against children and adolescents: a violation of human rights (Research, Society and Development, 2022)
Sexual violence against children and adolescents, in order to show the various forms of multifaceted manifestation and the ways to confront them, and points out the different types of violence, taking into account the advances made that recognized children and adolescents as subjects of rights and deserving of full protection. The aim of the study was to describe about violence. This is a narrative review composed of books and articles indexed in scientific data, using the Google Scholar database, SciELO, MEDLINE and PubMed. For inclusion, articles published in the period 2009-2019 were chosen. Using the DeCS: Child Abuse, Child and Adolescent Statute, Violence to Minors. Nine variables emerged to be studied. In view of the discussions raised, we can observe that the place of children and adolescents as subjects of rights was only possible with the evolution of society's thinking. For that, it was essential to change the paradigm. Children and adolescents, previously seen as objects of State intervention, only recently started to be considered human subjects worthy of full protection. In order for the actions to be actually protective, the articulation and co-responsibility of the family, state and society is essential.